Teacher quality standards: The differences in moral competency level among Malaysian teachers - Dzahir Kasa, Muhamad; Don, Yahya; Sofian Omar Fauzee, Mohd; Faiz Mohd Yaakob, Mohd (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2020)
The issue of quality standards for Malaysian teachers and the moral competency of teachers is a foundational part of the practice of Teacher Quality Standards in Malaysia and are fundamental to the formation of the Malaysian Education Development Plan (MEDP) 2013-2025. This paper discusses the level of teachers' moral competency and Teacher Quality Standards practice based on demographic factors (gender, age, class size, number of subjects taught, and school experience). This quantitative study used cross-sectional survey approach to collect data on current situation of moral competency and Teacher Quality Standards practice. A Stratified random and multistage sampling techniques were used to select 142 samples from the study population of teachers in National schools in Kedah, Perlis and Penang in Malaysia. The instruments used were the Moral Judgment Test (MJT) (Lind, 2000) and the College Teaching Behaviours Inventory (CTBI) (Braxton, & Bayer, 2003). The results showed significant differences in moral competencies based on age, gender, number of subjects taught, and teaching experience, and significant differences in terms of Teacher Quality Standards based on age, teaching experience, and number of subjects taught. These results provided a basic knowledge of the Teacher Quality Standards practice in national schools and its relationship to moral competency based on demographic and experience in school aspects. National school teachers who practiced Teacher Quality Standards demonstrated that they have the capacity for moral competency in self-governance by applying Teacher Quality Standards when making decisions and considerations in selecting ethical practices in developing national education in the future.